Parenting after Divorces: A Qualitative Research - رضا خجسته مهر; مسعود فلاحی خشکناب; سارا حجاری; منصور سودانی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: Parenting is one of the hardest tasks of parents and a determining factor in children’s psychological health. One of the factors influencing parenting is divorce. The objective of the present study was to examine parents’ experience of parenting after divorce. Methods and Materials: This qualitative study was conducted using descriptive phenomenology method. The statistical population in this study included men and women who had experienced parenting after divorce. The participants were 13 men and women who were chosen from among the clients of consultation centers using purposive sampling with maximum variation. They were invited for in-depth and exploratory interviews. Data were analyzed using seven-stage Colaizzi method. Findings: The analysis of these experiences led to the identification of the 10 major themes of parents’ relationship, parent’s individual needs, parent’s support network after divorce, parent’s attitude, emotions, and challenges, parent’s responsibility and supervision, parent-child maturity, and parent-child psychological damage in the parenting process. Conclusions: Parents describe parenting after divorce as a challenging task. The nature of the parents’ relationship, and their individual needs and support sources after divorce can influence their attitude and emotions towards parenting. Psychological damage, growth, and maturity are among the parents’ experiences during the parenting process after divorce.